Relationship between internal and external load in young italian high-level soccer players - Melis, M.; Nigro, F.; Marcora, S. M. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: In top-level soccer, monitoring training loads has become a fundamental method for achieving top performance (1). In the present study, the relationships between external and internal training loads variables were investigated in high-level Italian youth soccer.